Analysis of Regional Innovation Performance in Portugal - Results from an External Logistic Biplot Method - Purificacion Vicente Galindo; Teresa de Noronha Vaz; Peter Nijkamp; Eric de Noronha Vaz (Tinbergen Institute, 2011)
Portuguese strategic choices regarding innovation and R&D policy have, over the past two decades, produced various positive achievements, in which the regions of Lisbon and Algarve have taken the lead, and are the only ones in the country to converge towards the European average growth rate. Regarding the other Portuguese regions - despite significant national growth rates in the 1990s as well as a successful attempt to cope with the EMU -, these are lagging behind the EU average with respect to gross production, investment or employment generation. Meanwhile, one of the greatest public policy efforts was to diffuse much of the European funds across the entrepreneurial sector. After a long pathway, it is now timely to evaluate the firms' contribution to national and regional growth, their obstacles and impacts. For the purpose of this paper, innovation is used here as a major contributor to the policy evaluation process referred to above. Our investigation aims to explain the present performance of Portuguese firms located throughout the country and to explore those innovation determinants that have a region-specific connotation. To provide a thorough investigation, our analysis defines, on a regional basis, a set of firms' behavioural patterns regarding innovation. In our modelling, we employ a new methodology, viz. the External Logistic Biplot method, which is applied to an extensive sample of innovative institutions in Portugal. Variables such as 'Promoting knowledge', 'Management skills', 'Promoting R&D', 'Knowledge transfer', 'Promoting partnership & cooperation', and 'Orientation of public measures' have been identified as crucial determinants in earlier studies and are now used to describe regional institutional profiles. Such profiles exhibit a great variety in the way they combine these determinants to promote regional innovation. The creation of a gradient of capacity to dynamically innovate associated with each firm makes it possible to analyse the innovation gradient of each region in Portugal. Our paper presents and systematically investigates these findings and then reaches some policy conclusions.
urn:NBN:nl:ui:31-1871/38522
Keywords: O31; R11; 330; Innovation; Firms' Performance; Regional Innovation Systems; Principal Coordinates Analysis; External Logistic Biplot; Voronoi Diagram; Dissimilarity Matrix; Innovation; Unternehmenswachstum; Messung; Portugal